A note on cephalopods from the stomachs of Dall’s porpoises (Phocoenoides dalli) from the Northwestern Pacific and Bering Sea, 1978-1982 - Fiscus, Clifford H.; Jones, Linpa L. (J. Cetacean Res. Manage., 1999)
Cephalopod prey were identified from the stomachs of 100 Dall’s porpoise (Phocoenoides dali) incidentally taken by commercial salmon gillnets and research vessels from 1978 to 1982 in the western North Pacific Ocean and Bering Sea, Fighty-four porpoise were collected Fi June and Joly during the salmon fishing season; the remainder were collected in August-Sepiember. Seven cephalopod families Gnoploteuthidae, Onychoteuthidae, Gonatidae, Histioteuthidae, Chiroreuthidae, Cranchiidac and Rolitaenidae) were identified in the Stomachs. Gonatids were the most abundant, comprising 98% of the beaks. Gonatopsis borealis was the most abundant species, occurring in 85 stomachs, The gonatids occur in meso- and epipclagic waters and many approach the surface at night when the porpoise are feeding.